Meeting the challenge : informatics and medical education : proceedings of the IFIP-IMIA working conference on Meeting the Challenge: informatics and medical education Chamonix, France, 21-25 March, 1983 - Pagès, Jean-Claude; Levy, Allan H; Grémy, François; Anderson, John (North-Holland, 1983)
Report from the conference on medical informatics and medical education Chamonix, 1983.
Keywords: Education, Medical; International Cooperation; Curriculum; Medical Informatics; lékařská informatika; kurikulum; mezinárodní spolupráce; studium lékařství; Medical Informatics Computing; výchova a vzdělávání; lékařská počítačová informatika; Education